Metasurfaces Composed of Plasmonic Molecules: Hybridization Between Parallel and Orthogonal Surface Lattice Resonances. Issue 4 (9th December 2019) - Liu, Shao‐Ding; Yue, Peng; Zhang, Shi; Wang, Mingshan; Dai, Hongwei; Chen, Yiqin; Nie, Zhong‐Quan; Cui, Yanxia; Han, Jun‐Bo; Duan, Huigao
Abstract: Multiple surface lattice resonances suppress radiative losses effectively around several spectral positions, thereby enhancing the light‐matter interactions and making them promising for multiwavelength related applications, and it is important to develop reliable methods to generate multiple lattice resonances. In analogy to natural materials composed of various kinds of molecules, this study proposed to construct metasurfaces with plasmonic artificial molecules, which represent distinct collective responses compared with that of single nanoparticles. It is shown that sharp multiple surface lattice resonances are excited due to the coupling between the localized resonances of plasmonic trimer molecules and the Rayleigh anomalies of the array, and there is a rarely observed parallel lattice resonance caused by the formation of equivalent dipoles perpendicular to the polarization. Particularly, even though the parallel mode is weak, a pronounced anticrossing behavior due to the hybridization with the orthogonal mode occurs when the resonance energies are approaching to each other, which results in two hybridized eigenmodes that possess both characteristics of parallel and orthogonal Rayleigh anomalies. Considering the excitation of the lattice resonances in asymmetric environments, the flexible tunability, and the ability to tailor the collective responses, metasurfaces constructed with artificial molecules are promising platforms to design ultrafast and compact photonic devices. Abstract : This study proposes to construct metasurfaces with plasmonic artificial molecules, which show distinct collective responses compared with that of single nanoparticles. A rarely observed parallel surface lattice resonance and the conventional orthogonal modes are excited simultaniuously. Even though the parallel mode is weak, a strong hybridization with the orthogonal mode occurs when the two resonances are approaching to each other.